HOTAIRM1 Promotes Malignant Progression of Transformed Fibroblasts in Glioma Stem-Like Cells Remodeled Microenvironment via Regulating miR-133b-3p/TGFβ Axis - Wang, Haiyang; Li, Haoran; Jiang, Qianqian; Dong, Xuchen; Li, Suwen; Cheng, Shan; Shi, Jia; Liu, Liang; Qian, Zhiyuan; Dong, Jun (Frontiers in Oncology, 2021)
Recent studies have reported that cancer associated fibroblasts (CAFs) and glioma stem-like cells (GSCs) played active roles in glioma progression in tumor micro-environment (TME). Long noncoding RNAs (lncRNAs) have been found to be closely associated with glioma development in recent years, however, their molecular regulatory mechanisms on CAFs in GSCs remodeled TME kept largely unelucidated. Our study found that GSCs could induce malignant transformation of fibroblasts (t-FBs) based on dual-color fluorescence tracing orthotopic model. Associated with poor prognosis, Lnc HOXA transcript antisense RNA, myeloid-specific 1 (HOTAIRM1) was highly expressed in high-grade gliomas and t-FBs. Depleting HOTAIRM1 inhibited the proliferation, invasion, migration and even tumorigenicity of t-FB. Conversely, overexpression of HOTAIRM1 promoted malignancy phenotype of t-FB. Mechanistically, HOTAIRM1 directly bound with miR-133b-3p, and negatively regulated the latter. MiR-133b-3p partly decreased the promotion effect of HOTAIRM1 on t-FBs. Furthermore, transforming growth factor-β (TGFβ) was verified to be a direct target of miR-133b-3p. HOTAIRM1 can modulated TGFβ via competing with miR-133b-3p. Collectively, HOTAIRM1/miR-133b-3p/TGFβ axis was involved in modulating t-FBs malignancy in TME remodeled by GSCs, which had the potential to serve as a target against gliomas.